(untitled) (Journal of Contemporary Educational Policies and Practices, 2025)
Evaluation is the core component of the cyclical process for academic program administration. This paper aims to investigate learners’ evaluation of the constructive alignment (CA), i.e. alignment of course learning outcomes, teaching and learning activities, and assessment tasks, of a Master’s program in Teaching English as a Foreign Language (TEFL) in a Vietnamese public university. As direct beneficiaries, learners and their feedback and recommendations are considered for proper actions regarding programs’ quality assurance (QA) and administration. To achieve its aim, the current research applied a descriptive mixed-methods study, using a questionnaire and focus group interviews to collect relevant information. Thirty-four graduates from the studied program answered the questionnaire, which was adapted from the program assessment framework by ASEAN University Network Quality-Assurance (AUN-QA). Twelve of these participants joined two focus group interviews, which helped to gauge in-depth understanding of the participants’ feedback and recommendations regarding curriculum development and implementation. The findings reveal that the participants were satisfied with the CA of the program, ranking it as ‘an example of best practices’ (an equivalent to the top second level of AUN-QA’s quality scale). It was, however, suggested that the CA should be enhanced to better serve the program’s quality assurance and administration.